Circulating cytokine profile in anti-neutrophilic cytoplasmatic autoantibody-associated vasculitis: prediction of outcome? - Sophie Ohlsson; Jörgen Wieslander; Mårten Segelmark (Hindawi Limited, 2004)
AIMS: The anti-neutrophilic cytoplasmatic autoantibody-associated vasculitides (AASV) are diseases of relapsing-remitting inflammation. Here we explore the cytokine profile in different phases of disease, looking for pathogenic clues of possible prognostic value.